Modelagem de Aplicação EaD para Viabilização de Cursos Extracurriculares em Comunidades Remotas Utilizando uma Estrutura de Redes Orientadas a Plano de Deslocamento Contínuo - Silva, Mateus P.; Ponciano, Rafael de L.; Coelho, Raphael R. (Anais do Latin American Symposium on Digital Government (LASDiGov), 2012)
This paper proposes the modeling of a distributed system, named Lapras, in the area of Distance Education. Make use a network infrastructure CoDPON - Continuous Displacement Plan Oriented Network - inspired by DTN networks. This architecture aims at linking places without technological inclusion, such as the riverside communities of the Amazon, with large urban centers. The Lapras relies on voluntary to offer extracurricular courses for students registered in schools of communities provided with infrastructure CoDPON. This model is intended as a basis for future implementation of the Lapras in the Amazon's scene.